Control of election campaign accounts : Reading in Ordinance 01-21 on the organic law relating to the electoral system - Reddad, Noureddine (Journal of Human Sciences, 2022)
The issues of financing the election compains have a significant impact on the quality of elections, So the legislator intervened by Ordinance No. 21-01 containing the organic law relating to the electoral system to control and monitor the process of financing othe electoral campaigns by submitting the candidates '  electoral campaign accounts to the supervision of the Election Campaign Finance Supervisory Commission of the Independent National Electoral Authority Created for the first time under this law, in order to find a balance between two needs: to achieve at least an equality between the candidates, and ensuring the participation of all in the elections without their limited financial capacities being an obstacle to this, on the one hand, and on the other hand, conducting a fair and correct elections in an atmosphere of transparency, and it’s consequentce of the citizen's feeling that his vote is neither sold nor bought, otherwise a vote that is given to those who deserve it regardless of what the candidate has spent.